Mobile Learning Development Based on Android Application for Islamic Education - Sibilana, Annas Ribab; Hasanah, Uswatun; Laili, Anisatun Nur (Letters in Information Technology Education (LITE), 2020)
The Development of Android-Based Learning Media in Subject of Islamic Education for Grade XI in SMA Negeri 2 Malang was based on rapid development of technology, especially in field of communication gadget. Various advanced communication gadget called smartphone has been widely introduced in order to support our needs. Android-based Smartphone was very well-known up to among students. Besides, the fact of learning media for Islamic education was very least. Hence, it needed the development of android-based learning media for answering the challenge of globalization era which put forward a practical and fun information technology. The result of the development were (1) has detail explained the procedure of the development of android-based learning media (2) the development product has proved attractive and effective in increasing the students learning outcomes based on the results obtained from the questionnaire responded by validators, subject matter expert for 73.5%, 86.6% media expert, learning expert of 84.6%, and 88.1% from students responses.